Detection of Sugar Content in Fruit – Chemical Experiments in Kindergarten - Nazaruk, Stanisława; Klim-Klimaszewska, Anna (Studia Edukacyjne, 2020)
Experiments carried out by children are highly instructive adventures that develop interest in science. Nothing motivates a child to learn physics or chemistry more than experimentation. Supervised by their teachers, using safe reagents, chemical glass, and other equipment required to conduct experiments, “Little Scientists” discover the laws of physics and chemistry. Experimenting favors a search for answers to the most basic questions; it helps children see the magic of science and discover the secrets of the world around them. Contrary to the common opinion, holding that physical or chemical experiments may be introduced at the beginning of primary school at the earliest, preschool-age children are already prepared for such activities. The article presents a chemical experiment concerning sugar detection conducted by 6-year-olds. Research was performed to determine whether making chemical experiments has an impact on the level of children’s knowledge about sugars. The study included 20 children who carried out chemical experiments in four parallel groups. The level of knowledge was tested twice: first prior to the experiment and then following the experiment. The analysis of the data obtained demonstrated that after the experiment the level of children’s knowledge about sugars increased significantly, as evidenced by the t-Student Test outcomes.